Isobaric vapor-liquid equilibrium (VLE) of ternary lead–tin–antimony alloy system at 2 Pa - Xu, Junjie; Gao, Jingbao; Kong, Lingxin; Xu, Baoqiang; Yang, Bin; YOU, Yanjun (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
New experimental vapor-liquid equilibrium (VLE) data of the ternary lead-tin-antimony (Pb-Sn-Sb) alloy system are determined by using a new experimental method. The experimental VLE data passed the thermodynamic consistency test (Van Ness test), which indicates that the experimental results are reliable. The activities of components of the Pb-Sn-Sb ternary alloy and the corresponding three constituent binaries were calculated using the Wilson equation. The predicted values agree well with the experimental data, and the average relative deviation were smaller than ± 4.00 %, the average standard deviation smaller than ± 0.03 for all constituent binaries, which indicates that the Wilson equation is reliable for calculation of activity of components of Pb-Sn-Sb alloy system. The VLE data of Pb-Sn, Sb-Sn binary alloys, and Pb-Sn-Sb ternary alloy was calculated based on the Wilson equation and VLE theory. The calculated VLE are in good agreement with the experimental VLE data, indicating that this method is reliable for calculating VLE of alloy systems. This study offer a valid way to analyze the composition of product dependence on the temperature and pressure during the process of vacuum distillation, which will be of important guiding significance to vacuum distillation processes.